2015
DOI: 10.1371/journal.pone.0126803
|View full text |Cite
|
Sign up to set email alerts
|

Association between TLR2 and TLR4 Gene Polymorphisms and the Susceptibility to Inflammatory Bowel Disease: A Meta-Analysis

Abstract: BackgroundThe associations between toll-like receptor 2 (TLR2) and toll-like receptor 4(TLR4) polymorphisms and inflammatory bowel disease (IBD) susceptibility remain controversial. A meta-analysis was performed to assess these associations.MethodsA systematic search was performed to identify all relevant studies relating TLR2 and TLR4 polymorphisms and IBD susceptibility. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated. Subgroup analyses were performed by ethnicity and publication quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 58 publications
1
40
0
2
Order By: Relevance
“…Similarly, previous results have concluded that TLR2 (either TLR2/1 or TLR2/6) and TLR4 activation decrease significantly 5-HT uptake in Caco-2/TC7 cells [21,22]. Moreover, the over-expression of both receptors has been implicated in IBD [14]. Accordingly, we have analyzed the possible interaction between TLR2 and TLR4 with NOD2.…”
Section: Interdependence Among Tlr2 Tlr4 and Nod2 In Caco-2/tc7 Cellssupporting
confidence: 59%
See 1 more Smart Citation
“…Similarly, previous results have concluded that TLR2 (either TLR2/1 or TLR2/6) and TLR4 activation decrease significantly 5-HT uptake in Caco-2/TC7 cells [21,22]. Moreover, the over-expression of both receptors has been implicated in IBD [14]. Accordingly, we have analyzed the possible interaction between TLR2 and TLR4 with NOD2.…”
Section: Interdependence Among Tlr2 Tlr4 and Nod2 In Caco-2/tc7 Cellssupporting
confidence: 59%
“…PRRs are expressed in intestinal epithelial cells [11,12] and are able to recognize microbial-associated molecular patterns (MAMPs) to develop either inflammatory or tolerance responses [13]. In this context, several studies have reported that numerous PRRs, as TLR2, TLR4 [14] and NOD2 [15], seem to be implicated in IBD due to the dysfunctional recognition of commensal microbiota [16]. TLR2 is expressed in the cell surface and can detect molecular patterns associated with Gram-positive bacteria [17] through their heterodimers (TLR2/1 and TLR2/6) [18] while TLR4, also located on the cell surface, detects lipopolysaccharide (LPS), the major cell wall component of Gramnegative bacteria [19].…”
Section: Introductionmentioning
confidence: 99%
“…Persons with this TLR4 haplotype are less responsive to LPS and have an increased risk of severe infection by gram-negative bacteria (22), as well as of chronic inflammatory bowel disease (23). rs4986790 may protect against malaria (24), yet increases the global cancer risk (25).…”
Section: Loss-of-function Polymorphism In Tlr4mentioning
confidence: 99%
“…It is noteworthy that the common variants in TLR3 and TLR4 that worsen the prognosis of breast cancer patients also affect the susceptibility to a variety of infectious disease. As a possibility, human populations who are heterogeneous in the function of these PRRs might have the evolutionary advantage that portions of them are protected against lethal or chronic infection by specific microorganisms (22)(23)(24), explaining why SNPs affecting major PRRs have been maintained over evolution. To our knowledge, no study has linked rs867228 in FPR1 to a particular disease.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Through a combination of all the available published data, it is hypothesized that a meta-analysis with increased statistical power might allow causative genes to be identified and plausible candidate genes to be excluded with reliability. Although there have been some meta-analyses focus on TLR4 polymorphism and CD, the relationship between TLR4 T399I gene polymorphism and the susceptibility to CD is controversial [20, 21]. Therefore, we conducted the present meta-analysis to quantitatively assess this relationship.…”
Section: Introductionmentioning
confidence: 99%